Doctoral Dissertations in Economics One-Hundred-Tenth Annual List (Journal of Economic Literature, 2013)
The list below specifies doctoral degrees conferred by U.S. and Canadian universities during academic year July 2012 to June 2013. Lists of degree recipients and subject classifications are provided by the university. Note: Dissertations without classifications may be found under “Y Miscellaneous Categories.”